Identification of Plasma Fatty Acids in Four Lipid Classes to Understand Energy Metabolism at Different Levels of Ketonemia in Dairy Cows Using Thin Layer Chromatography and Gas Chromatographic Techniques (TLC-GC) - Fiore, Enrico (Animals (Basel), 2020)
SIMPLE SUMMARY: Dairy cows with a high milk production require an excessive amount of energy in the first phase of lactation. Different metabolic processes are involved to reach the high energy requirement, in particular the mobilization of the adipose tissue which could lead to the development of metabolic diseases, such as subclinical ketosis. Early detection of excessive lipid mobilization could improve the health status of animals and reduce economic losses in farms. The aim of this research is to identify the plasma fatty acids in four lipid classes in order to understand energy metabolism at different levels of ketonemia in dairy cows using Thin Layer Chromatography and Gas Chromatographic techniques (TLC-GC). The research establishes the concentrations of fatty acids, belonging to four plasma lipid classes, in animals with different degrees of hyperketonemia. ABSTRACT: Excessive mobilization of adipose tissue in high milk producing dairy cows predisposes to metabolic diseases. The aim of this research was to identify the plasma fatty acids in four lipid classes as biomarkers for the diagnosis of hyperketonemia in bovines using thin layer chromatography and gas chromatographic techniques (TLC-GC). Sixty multiparous Holstein–Friesian dairy cows were enrolled in the study. Blood samples from the coccygeal vein were collected and β-hydroxybutyrate (BHB) was evaluated. All animals were divided into three groups on the basis of ketonemia: BHB < 0.50 mmol/L, 0.50 < BHB < 1.0 mmol/L, and BHB > 1.0 mmol/L. Plasma fatty acid concentrations were evaluated in four lipid classes: Free Fatty Acids (FFA), Triglycerides (TG), Cholesterol Esters (CE) And Phospholipids (PL). The concentration of fatty acids was analyzed using TLC-GC. The results showed the following significance in the lipid classes: 19 fatty acids were significant (p < 0.053) in FFA, nine fatty acids were significant (p < 0.050) in TG, eight fatty acids were significant (p < 0.050) in CE and three fatty acids were significant (p < 0.049) in PL. Eleven parameters were considered as predictive fatty acids related to animals in hyperketonemia. The FFA increased simultaneously with blood BHB levels, although the identified predictive fatty acids related to the TG and CE lipid classes decreased, meanwhile the BHB values increased. In the PL lipid class, no fatty acids were predictive.